The Relationship Between Teacher Job Stress and Burnout: A Moderated Mediation Model - Zhao, Weiguo; Liao, Xiangrui; Li, Qingtian; Jiang, Wenning; Ding, Wen (Frontiers in Psychology, 2022)
This study explored the relationship between teacher job stress and job burnout using a sample of 558 primary and secondary school teachers, who were administered a teacher job stress scale, teacher job burnout scale, work–family conflict questionnaire, and general self-efficacy scale. The results showed that: (1) job stress had a significant predictive effect on work–family conflict and job burnout; (2) work–family conflict played a mediating role in the relationship between job stress and job burnout; (3) self-efficacy was found to play a moderating role in work–family conflict and job burnout. However, this indirect effect was stronger for teachers with high self-efficacy, which means that the protective effects of self-efficacy were limited. These findings add to research on the relationship between teacher job stress and job burnout, and provide ideas for teachers to balance work–family relationships and reduce job burnout.